Correction: Olaguer et al. Landfill Emissions of Methane Inferred from Unmanned Aerial Vehicle and Mobile Ground Measurements. Atmosphere 2022, 13, 983 - Eduardo P. Olaguer; Shelley Jeltema; Thomas Gauthier; Dustin Jermalowicz; Arthur Ostaszewski; Stuart Batterman; Tian Xia; Julia Raneses; Michael Kovalchick; Scott Miller; Jorge Acevedo; Jonathan Lamb; et al. (Atmosphere)
There was an error in the original publication [...]